THE RELATIONSHIP BETWEEN THE LEVEL OF KNOWLEDGE OF PULMONARY TB PATIENTS AND HEALING RATE THROUGH DOTS TREATMENT STRATEGY AT PKM SUKAINDAH BEKASI REGENCY IN 2024 - Nurhayati, Eli; Barkah, Asep (HEARTY, 2025)
A global health problem that is still relevant today is pulmonary tuberculosis (TB). Pulmonary tuberculosis, better known as TB, is a disease that has been around for a long time, triggered by pathogenic bacteria, and has never received adequate treatment. One effort in treating pulmonary TB is the DOTS strategy. The results of interviews with 5 pulmonary TB patients, most of whom stated that they did not know enough about pulmonary TB disease and did not regularly take their medication. Objective: to determine the relationship between the level of knowledge of pulmonary TB patients and the rate of recovery through the DOTS treatment strategy at PKM Sukaindah, Bekasi Regency in 2024. Quantitative research design with a descriptive correlational (cross-sectional) approach. The sample was 75 pulmonary tuberculosis patients who had received treatment for at least 6 months. The analysis used is univariate and bivariate analysis with the chi-square test. The results showed that the majority of respondents had good knowledge about pulmonary TB (73.3%), and the majority of respondents were declared cured of TB disease through the DOTS treatment strategy (65.3%). The results of the chi-square test show that there is a relationship between the level of knowledge of pulmonary TB patients and the cure rate through the DOTS treatment strategy (p-value: 0.001) and the OR value (6.000). Conclusion: there is a relationship between the level of knowledge and the cure rate for pulmonary TB patients. so it is hoped that health workers will pay attention to the condition of patients with insufficient knowledge/understanding about the importance of the pulmonary TB treatment process by providing further health services.